Economic Determinants and Information Environment Effects of Earnouts: New Insights from SFAS 141(R) - CADMAN, BRIAN; CARRIZOSA, RICHARD; FAUREL, LUCILE (Journal of Accounting Research, 2014)
ABSTRACT Contingent considerations (earnouts) in acquisition agreements provide sellers with future payments conditional on meeting certain conditions. Prior research provides evidence that acquiring firms use earnouts to minimize agency costs associated with acquisitions. Using earnout fair value information, recently mandated by SFAS 141(R), we provide new insights into the economic determinants to include earnout provisions in acquisition agreements, including motivations to resolve moral hazard and adverse selection problems, bridge valuation gaps, and retain target firm managers. We document variations in initial earnout fair value estimates and earnout fair value adjustments that correspond with these underlying motivations. We also provide evidence that target managers stay longer with the firm after the acquisition when earnouts are included primarily to retain target managers. Finally, we demonstrate that earnout fair value adjustments required by SFAS 141(R) provide valuable information to market participants and are negatively associated with the likelihood of contemporaneous and future goodwill impairments.